The Mahakal Temple - Temples of India Project Team (Jio Institute, 2024)
The surviving shrine, known as the Mahakal Temple, presently consists of an open mandapa with modern steel railing, situated in front of the original garbhagriha. The temple can be reached by flights of steps which are flanked by carved pillars. The base of the mandapa is old, evident from the old vedibandha, which is refloored with modern tiles. There is a nandi (the bull vehicle of Shiva) in the mandapa, facing the main sanctum.